Strategic Optimization to Enhance Effective Jetty Operations at Kertapati Port - Sukmadanu, Luthfi; Utama, Akbar Adhi (Community Engagement and Emergence Journal (CEEJ), 2025)
This study addresses operational challenges at Kertapati Port, where barge delays, poor stakeholder coordination, and lengthy administrative processes hinder efficiency. Using the Current Reality Tree (CRT) analysis, the research identifies root causes that reduce jetty throughput and extend vessel waiting times, leading to higher operational costs. To overcome these issues, three solutions were proposed: (1) developing integrated Standard Operating Procedures (SOPs) for berthing/unberthing and administration, (2) adding standby tugboats to ensure smoother berthing operations, and (3) decentralizing administration through an operational office at the jetty. The Analytical Hierarchy Process (AHP) was applied to prioritize these alternatives, while financial feasibility was evaluated using Net Present Value (NPV) and Internal Rate of Return (IRR). Results indicate that implementing integrated SOPs is the most effective solution, significantly reducing idle time and enhancing loading and unloading processes. A 2025 field trial of draft SOPs improved coal loading efficiency to an average of 500 MT/hour, with potential for notable annual throughput growth. Cost simulations suggest savings of thousands of USD per month, mainly by lowering demurrage costs. Furthermore, a real-time digital monitoring system has improved coordination, administrative speed, and schedule accuracy. The study recommends continuous evaluation using Key Performance Indicators (KPIs) and the Theory of Constraints (TOC) to sustain improvements and foster future innovations.